An application of the 'Made in Perak: history & tradition': theme in the Final Year Student Project (FYP) for Diploma in Fashion Design - Md Nor, Zainudin; Jaafar, Zaharah; Dahaman, Rizal Azni; Mustapha, Azwady; Ibrahim, Nur Idayu (2024)
This paper conducts an exploratory investigation into the FYP, Diploma in Fashion Design, Faculty of Art and Design, UiTM Perak Branch. In the September 2019-January 2020 academic session, 16 final semester students from group 5A were involved in this project. The author, who is one of the lecturers who teach the design course, has set the theme 'Made in Perak: History & Tradition' as a guide for students to find sources of inspiration. Before the class starts, an initial discussion session is held between the lecturers to ensure that all matters related to the final project can be coordinated such as project brief, project quantity, project proposal presentation schedule, continuous evaluation and monitoring aspects. .